'Professional Inefficacy is the Exact Opposite of the Passionate Social Worker': Discursive Analysis of Neoliberalism within the Writing on Self-care in Social Work. Issue 1 (2nd January 2021) - Stuart, Heather
ABSTRACT: Social work experiences notable rates of burnout and subsequent attrition. In the social work academic and practice-based literature, self-care strategies are proposed as a means of mitigating the effects of workplace stress and feelings of emotional exhaustion. However, the neoliberal self-care discourse intended to alleviate feelings of distress may in fact be exacerbating professional burnout. Yet discourse analysis allows for a critical examination of neoliberalism's discourse of social worker self-care.